Development of a Growth School-Based Academic Leadership Model to Improve Teacher Professionalism and Student Achievement - Annerlie Putri Agung; Sudarwan Danim; Nurul Astuti Yensi (GHAITSA : Islamic Education Journal, 2025)
School leadership plays a strategic role in improving the quality of teaching and student achievement. However, in many educational institutions, school leadership practices are still predominantly administrative and have not optimally supported the continuous professional development of teachers. This study aims to develop a Growth School-based academic leadership model to enhance teacher professionalism and student achievement. The study employed a Research and Development (R&D) approach by adapting the Borg and Gall development model integrated with the Educational Design Research framework. The research participants consisted of 33 teachers and 250 students from a secondary school. Data were collected through observation, interviews, questionnaires, and documentation. Data analysis applied a mixed-methods approach combining descriptive quantitative analysis and thematic qualitative analysis. The findings indicate that the implementation of the Growth School leadership model, which is built upon three main pillars, namely collaborative, reflective, and innovative leadership, significantly improved teacher professionalism from 70% to 95%. This improvement also contributed to better learning quality and increased student achievements in both academic and non-academic fields. The novelty of this research lies in integrating the concept of growth mindset into academic leadership practices to foster an adaptive and sustainable professional learning culture within schools.